Hubungan Model Pembelajaran Project Based Learning terhadap Kreativitas dalam Pembuatan Pouch Bag Recycle di SMK Negeri 3 Probolinggo - Isna Yuniarti Shalehah; Deny Arifiana; Ma’rifatun Nashikhah; Imami Arum Tri Rahayu (Departement of Mathematics Education, 2024)
The objectives of the research conducted at vocational high school 3 Probolinggo are: 1) to know the implementation of project based learning models, 2) to find out the levels of creativity in making pouch bag recycle, 3) to find out the relationship between project based learning models and creativity in making pouch bag recycle at vocational high school 3 Probolinggo. The research conducted was quantitative research. The sample consisted of 31 students of class XI fashion 2. The approach used was purposive sampling. Questionnaires and observation were the data collection techniques used. SPSS 25.0 program was used for product moment correlation method with 5% significance. The results showed at: 1) the implementation of the project based learning model in the good category with a percentage of 88%, 2) the level of creativity in making pouch bag recycle is in a high category with a percentage of 100%, 3) there is a relationship between the project based learning models on creativity in making pouch bag recycle with significance value (2-tailed) is 0,021 (0,021 < 0,05). Pearson correlation value is 0,413 > 0,355.